In vitro attrition wear resistance of four types of paste-like bulk-fill composite resins - Faeze Asadian; Amirahmad Pahlavan Hoseini; Leila Ahmadian; Niyousha Rafeie; Samaneh Rezaei; Zohreh Moradi (BMC, 2022)
Abstract Background Recently, the application of bulk-fill composite resins has increased significantly. Attrition wear and the consequently increased surface roughness of composite resins are among the causes of restoration failure in the posterior teeth. This study aimed to compare the attrition wear and surface roughness of four types of bulk-fill composite resins compared to a conventional composite resin. Methods EverX-Posterior, X-tra fil, SonicFill 2, and Filtek Bulk-Fill composites (bulk-fill) and Z250 composite (conventional resin composite) were evaluated. Thirty cylindrical specimens (n = 6) were weighed and monitored for 24 h until their weight was stabilized. The primary surface roughness of the specimens was measured by a profilometer. The specimens were then subjected to attrition wear in a chewing simulator. Next, the specimens were weighed, and the surface roughness was measured again. Data were analyzed by one-way ANOVA and Tukey's post-hoc test at P < 0.05 significance level. Results According to one-way ANOVA, the difference in weight loss was significant among the groups (P = 0.004) but the difference in surface roughness of the groups was not significant after the attrition wear (P > 0.05). Tukey's post-hoc test showed that the weight loss of bulk-fill composites was not significantly different from that of Z250 conventional composite after the attrition wear (P > 0.05). Conclusion Within the limitations of this study, it appears that the tested bulk-fill composite resins are comparable to the conventional composite regarding their attrition wear, increased surface roughness, and weight loss.